VZV Prophylaxis After Allogeneic Hematopoietic Stem Cell Transplantation in Children: When to Stop? - Eva deBerranger; Anne‐Flore Derache; Nassima Ramdane; Julien Labreuche; Pauline Navarin; Fanny Gonzales; Wadih Abou‐Chahla; Brigitte Nelken; Bénédicte Bruno (Cancer Reports)
ABSTRACT Background Acyclovir treatment is an efficient prophylaxis to prevent varicella‐zoster virus (VZV) reactivation after allogeneic hematopoietic stem cell transplantation (HSCT). Aims This single center retrospective study tried to determine if the lymphocytes immunophenotyping could help to determine the duration of prophylaxis, and evaluated complications, and associated risk factors for VZV infection. Methods and Results Eighty‐four children underwent an allogeneic HSCT, in which 77 received an acyclovir prophylaxis. Twenty‐one of the 77 had a VZV infection with an incidence rate of 1.30 per 100 patients‐months (exact 95% CI, 0.81 to 2.01). Among these 21 patients with VZV infection, 16 had an infection after withdrawing acyclovir prophylaxis within a median of 49 days (range, 11 days–5.8 months). Thirty‐five percent of the VZV infected patients were hospitalized, 9% had a visceral dissemination, and 9% had postherpetic neuralgia. In multivariate analysis, higher VZV infection rate was associated with conditioning regimen with total body irradiation, immunoglobulin substitution, and antithymocyte globulin. The incidence of VZV infection increased significantly when patients had a CD4+ lymphocytes count below 23% (cHR 3.28 [95% CI, 1.09–9.81]; p = 0.03) or a CD4+/CD8+ ratio less than 0.9 (cHR 3.13 [95% CI, 1.04–9.36]; p = 0.04) at the time of stopping acyclovir prophylaxis. Conclusion After cessation of acyclovir prophylaxis, VZV reactivation can occur and be responsible for morbidity after allogeneic HSCT. This study suggests that the proportion of CD4+ lymphocytes and the CD4+/CD8+ ratio can inform decisions about the duration of acyclovir prophylaxis after allogeneic HSCT to prevent VZV reactivation.